An expert system for selection of sites for location of industries - Kabashi, Nassereldin; Ahmadun, Fakhru'l-Razi; Muyibi, Suleyman Aremu; Salami, Momoh Jimoh Emiyoka (Asian Network for Scientific Information, 2006)
All living creatures need air to survive. The number of pollution complaints received by the Department of Environment (DOE) has been rising steadily and has far exceeded other complaints; a few air pollutants can injure health, harm the environment and cause property damage. Due to shortage of manpower it is very difficult to verify that the developer actually complied with the approved Environmental Impact Assessment (EIA) guidelines. In (EIA) reports, the study to identify, predict and evaluate the impacts on the environment of any proposed project and to detail out the mitigating measures must be corrected out prior to the project approval and implementation. This study utilizes the application of a computer technology in the form of an expert system for the selection of industries in accordance to the air pollution index control. Some appropriate rules for structuring and implementing optimal air quality standards using CLIPS helps in the analysis and management of EIA information would also be examined.